Assessment of the Proportion of Recent HIV-1 Infections in Newly-Diagnosed Cases in Ghana - Matsuoka, Saori; Adusei-Poku, Mildred Asumamaa; Abana, Christopher Zab-Yen; Duker, Ewurabena Oduma; Bonney, Evelyn Yayra; Ofori, Sampson Badu; Parbie, Prince Kofi; Okazaki, Midori; Kawana-Tachikawa, Ai; Ishikawa, Koichi; Ampofo, William Kwabena; Matano, Tetsuro (Japanese Journal of Infectious Diseases, 2022)
Accurate monitoring of epidemics is a key strategy for controlling human immunodeficiency virus type-1 (HIV-1) infection. To delineate the characteristics of newly diagnosed cases of HIV-1 infection, we assessed the proportion of recent HIV-1 infections using a recent infection-testing algorithm (RITA). In 2015, 248 cases were newly diagnosed with HIV infection at the Regional Hospital Koforidua, Ghana. Of these, 234 cases (94.4%) were infected with HIV-1 only, four (1.6%) were infected with HIV-2 only, and 10 (4.0%) were co-infected with HIV-1 and HIV-2. All HIV-1 single-seropositive samples were used in the HIV-1 LAg avidity assay for RITA. Our analysis revealed that 18 cases (7.7%) were recently infected, indicating that early diagnosis was not achieved in Ghana. This is the first report to assess the proportion of recent infections in Ghana using a biomarker approach. The accumulation of these data will contribute to the accurate estimation of HIV-1 incidence and prevalence in Ghana.